Analysis of the Carrying Capacity and Land Capacity for Residential Areas in the Southern Part of Medan City - Kodri Sitompul; Cut Nuraini; Abdiyanto Abdiyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The increasing population triggers a demand for land for housing and other activities. Along with this, issues arise regarding the limited availability of land, especially in rapidly developed areas. This limitation has the potential to create an imbalance between the growing need for space and the existing land capacity. This study evaluates the land carrying capacity in four sub-districts in the southern part of Medan City, namely Medan Tuntungan, Medan Johor, Medan Amplas, and Medan Denai, in dealing with the continuously growing population. Using a spatial analysis approach with ArcGIS 10.8 software and detailed spatial data, this research identifies potential areas for residential development and projects the capacity of land to accommodate future populations. The analysis covers physical and environmental aspects such as land slope, soil type, natural disaster risks, and access to public facilities. The results show that each sub-district has different potentials and challenges. Medan Tuntungan, with its large area and flat land conditions, shows significant potential for residential development, although attention must be given to the existence of protected areas and agricultural land that must be preserved. Medan Johor, as an economic center, faces substantial pressure on land use, with some areas nearing their maximum capacity. Medan Amplas and Medan Denai, which are more urban, experience stricter land limitations. Population growth projections indicate a significant increase in land demand in some sub-districts in the coming decades. Without effective management, this has the potential to exert high pressure on the environment and urban infrastructure. This research emphasizes the importance of spatial planning and sustainable development policies to maintain a balance between housing needs and environmental conservation.